2017
DOI: 10.1186/s12907-017-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial carcinoma: a case report of a rare tumor of the larynx

Abstract: BackgroundLymphoepithelial carcinoma is a tumor mostly diagnosed in the nasopharynx, but it has also been described in a variety of nonnasopharyngeal sites. It is extremely rare in the larynx and should be distinguished from squamous cell carcinoma. Therefore, it must be known by clinicians, pathologists and oncologists. In this case report, we discuss its etiopathogeny, its epidemiological, clinical, pathological and therapeutic aspects, and its outcome.Case presentationAn 81-year-old Morrocan man, smoker for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…A variety of other names have also been attributed to this tumor category, such as undifferentiated carcinoma of nasopharyngeal type, undifferentiated carcinoma with lymphoid stroma, lymphoepithelioma and lymphoepithelial like carcinoma, as well as recent names like lymphoepithelial carcinoma (LEC). Recently, Acuna, Hammas and Kermani have highlighted the etiopathogenesis of the disease in the background of viral etiology [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of other names have also been attributed to this tumor category, such as undifferentiated carcinoma of nasopharyngeal type, undifferentiated carcinoma with lymphoid stroma, lymphoepithelioma and lymphoepithelial like carcinoma, as well as recent names like lymphoepithelial carcinoma (LEC). Recently, Acuna, Hammas and Kermani have highlighted the etiopathogenesis of the disease in the background of viral etiology [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of the search was 36 studies, of which 8 were excluded due to descriptions of different histologies, while 7 were removed due to the presence of LECs in sites other than the larynx or hypopharynx. After a comprehensive review, 21 articles were identified in the English literature from 1968 to 2018 [ 1 , 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Clinical information, including demographics, tumor location (sub-site), presenting symptoms, treatment modalities, viral etiology, genetic mutations and survival status, were extracted ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…6,8,11 Smoking, chewing tobacco, human papillomavirus, and alcoholism do not seem to be associated with LEC. 13 Nasopharyngeal carcinoma, undifferentiated type shares the same histopathologic features as SLEC. Some authors have reported a relatively less prominent lymphoplasmacytic infiltration in SLEC which we noticed in our case as well (Figure 2A and C).…”
Section: Discussionmentioning
confidence: 99%
“…4 But further studies are lacking to confirm the same. 10 Macroscopically, the tumor forms a mass that may or may not be ulcerated. Diagnosis can be challenging because the tumor may arise from hidden, submucosal sites.…”
Section: Discussionmentioning
confidence: 99%